Escrituras de mujer - Martínez, María Victoria; Milanesio, Adriana Cecilia; Novo, María del Carmen; Cúrtolo, Mónica Lucía; Gianotti, Ana María Angélica; Giacobone, Cristina Andrea; Sánchez, Rocío; Paruzzo, Pilar; Moscoso, Marcia; Bonnet, Marcela; Sosa, Cristina; García, María Fernanda; et al. (2023)
Fil: Martínez, María Victoria. Universidad Nacional de Córdoba. Facultad de Filosofía y Humanidades. Escuela de Letras; Argentina.